Natural and human hazard assessment of the archaeological sites of Paphos area (Cyprus) with the use of remote sensing and GIS. - Alexakis, D. D.; Agapiou, A.; Themistocleous, K.; Lysandrou, V.; Sarris, A.; Hadjimitsis, D. G. (Bulletin of the Geological Society of Greece, 2013)
The study focuses on the creation of an innovative methodology for the development of a risk assessment model for the archaeological sites of western Cyprus (Paphos district). On site observation is the most common way for monitoring cultural heritage sites and monuments in Cyprus. However, this procedure which includes data collection, periodical observations, and multivariate risk assessment analysis, is practically difficult to be accomplished with the traditional practices and methods since it is time consuming and cost insufficient. Thus, the use of modern technologies such as Remote Sensing and GIS is anticipated to provide a tool of directives for the protection and preservation of cultural heritage sites from anthropogenic and environmental threats. These technologies provide to scientists integrated monitoring capabilities and have the unique advantage to store and manipulate a large amount of spatial and attribute data simultaneously. This study aims to integrate both satellite remote sensing techniques and GIS in a multidisciplinary approach, for monitoring natural and anthropogenic hazards with the use of archived and up-to-dated multi-temporal remotely sensed images in the study area, namely in areas nearby cultural heritage sites and monuments in Paphos area (Cyprus).According to the results, extensive construction and building development has taken placein the broader area. It was also proved that vast number of sites is established on areas prone to erosion and landslide phenomena.